1993
DOI: 10.1212/wnl.43.10.2099
|View full text |Cite
|
Sign up to set email alerts
|

Reduced basal ganglia volume in HIV‐1‐associated dementia

Abstract: Although brain atrophy is a common neuroradiologic and pathologic finding in patients with HIV-1 infection, especially those with HIV-1-associated dementia complex, it is not clear whether specific regions of the brain are differentially responsible for tissue loss. In this study, we measured volumes of basal ganglia structures on MRIs for three groups: HIV-1-infected homosexual men with HIV-1-associated dementia complex (HIV+ demented), HIV-1-infected homosexual men without HIV dementia (HIV+ nondemented), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
186
2
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(205 citation statements)
references
References 0 publications
16
186
2
1
Order By: Relevance
“…Oster et al (1993) demonstrated remarkable atrophy in the central brain nuclei (including striatum and thalamus) and cerebral white matter on examination of autopsied HIV-infected brains. Aylward et al (1993) demonstrated volumetrically that basal ganglia volumes were smaller in demented AIDS patients than non-demented or control subjects. Immunohistochemically, Kure et al (1990) found that HIV antigens were more numerous in the globus pallidus than in other sites.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Oster et al (1993) demonstrated remarkable atrophy in the central brain nuclei (including striatum and thalamus) and cerebral white matter on examination of autopsied HIV-infected brains. Aylward et al (1993) demonstrated volumetrically that basal ganglia volumes were smaller in demented AIDS patients than non-demented or control subjects. Immunohistochemically, Kure et al (1990) found that HIV antigens were more numerous in the globus pallidus than in other sites.…”
Section: Discussionmentioning
confidence: 93%
“…However, there is a still a lack of detailed 3D maps that show the profile of HIV-associated changes throughout the brain. More conventional volumetric studies were the first to demonstrate global white matter atrophy, basal ganglia volume loss, and ventricular enlargement (Aylward et al, 1993;Hall et al, 1996;Stout et al, 1998). Nevertheless, volumetric studies are generally labor-intensive and cannot visualize the profile of deficits at the voxel level.…”
Section: Introductionmentioning
confidence: 99%
“…This line of investigation was initiated early in the HIV pandemic and quickly established a variety of pathological effects observable in vivo. The most common findings included regional gray matter atrophy, particularly in the basal ganglia [4][5][6], Electronic supplementary material The online version of this article (doi:10.1007/s13311-010-0010-4) contains supplementary material, which is available to authorized users. white matter lesions [7,8], ventricular expansion [9], and global cerebral atrophy [7,[10][11][12].…”
Section: Structural Magnetic Resonance Imagingmentioning
confidence: 99%
“…In particular, volumes of the basal ganglia are commonly decreased in HIV-infected patients [4-6, 13, 14] and have been shown to be associated with cognitive function [4,15] and biomarkers of HIV progression [16,17]. Specifically, atrophy of the caudate has been widely reported [6,15,18,19] and found to be associated with cognitive [5,20] and motor [21] dysfunction as well as lower CD4 T-cell counts [17].…”
Section: Structural Magnetic Resonance Imagingmentioning
confidence: 99%
“…In adult patients the clinical presentation is usually a combination of cognitive, motor, and behavioral dysfunction, often associated with MRI or CT evidence of cortical atrophy and disproportionate loss of volume in the basal ganglia [3]. The counterpart in infants and children is loss of developmental milestones, symmetrical pyramidal (or extrapyramidal) motor abnormalities, and impaired brain growth [2].…”
mentioning
confidence: 99%